CO2 methanation over the Ni-based catalysts supported on nano-CeO2 with varied morphologies. (1st January 2023) - Bian, Yufang; Xu, Chunying; Wen, Xueying; Xu, Leilei; Cui, Yan; Wang, Shuhan; Wu, Cai-e; Qiu, Jian; Cheng, Ge; Chen, Mindong
Graphical abstract: Highlights: The CeO2 supports with varied morphologies were prepared by the hydrothermal method. The morphology effect of these Ni/CeO2 catalysts were investigated. The 5Ni/NPs catalyst showed the most excellent low-temperature performance. The apparent activation energies of the catalysts were studied by the kinetic study. Online TPSR and in-situ DRIFTS of CO2 methanation used to reveal reaction mechanism. Abstract: A series of CeO2 supports with particular morphologies (nanorods, nanocubes, nanooctas, and nanoparticles) were successfully fabricated by controlling the parameters of the hydrothermal method. The obtained nano-CeO2 materials were utilized as the supports of the Ni-based CO2 methanation catalysts prepared by the incipient impregnation method. It was found that the catalyst supported on the CeO2 nanoparticles (5Ni/NPs) exhibited much higher catalytic activity and better stability than those of catalysts with other morphological CeO2 supports. Thus, the catalytic performance of Ni/CeO2 catalysts could be facilely tuned and optimized by precisely designing the morphology of the CeO2 support. The XPS, CO2 -TPD, and H2 -TPR characterizing techniques showed that Ni-based catalysts supported on nano-CeO2 with varied morphologies displayed different catalytic performances. It was supposed that the typical merits, such as the abundant oxygen vacancy, medium basic sites, moderate metal-support interaction, excellent reduction ability, etc., were considered as the main origins for the enhancement of the low-temperature catalytic activities. Furthermore, the kinetic study revealed that the Ni-based catalysts supported on the nano-CeO2 with varied morphologies performed the different apparent activation energies toward CO2 methanation. The specific reaction intermediates and possible reaction pathways were carefully investigated through the in-situ DRIFTS and online TPSR techniques. Overall, this work would provide new perspectives that the roles of the morphology effect of the support ought to be emphatically considered when designing new catalysts.